IA.LJ.FHA Efektivitas Teknik Mind Mapping Terhadap Kemampuan Higher Order Thinking Skill Pada Siswa Kelas VIII di SMP Negeri 8 Mataram Tahun Pelajaran 2022/2023 - Ismul Azam; Lalu Jaswandi; Farida Herna Astuti (Yayasan Masyarakat Cita Insani (YAMACITA): Bergerak Dibidang Penelitian, Pendidikan, Pelatihan, Reasearch, 2025)
Abstract: Higher Order Thinking Skill is the ability to think critically, logically and creatively which includes the ability to analyze, evaluate and create. The problem in this research is the low ability of students to think at a high level, this has a negative impact on students considering that HOTS skills are important in facing the industrial revolution in the 21st century era. The purpose of this research is to determine the effectiveness of the Mind Mapping Technique on Students' Higher Order Thinking Skills. The design of this research is a quasi experiment nonequivalent control group design. With a population of 239 students, and a sample of 10 people with low HOTS abilities based on pre-test results. The data collection technique used was purposive sampling. The data collection methods used were questionnaires as the main method, observation methods, interviews and documentation as complementary methods. Data analysis uses the T-test formula. Based on the results of data analysis, the tcount value was (6.485), while the t-table value at the 5% significance level was (2.262). Because t-hitung is greater than the ttable value (6,485 > 2.262), then Ho is rejected and Ha is accepted. So the results of this research show that the Mind Mapping Technique is effective for the Higher Order Thinking Skills of Class VIII students at SMP Negeri 8 Mataram for the 2023 academic year.